I always, always get my way - Krasnesky, Thad (Flashlight Press, 2009)
A rhyming text tells the story of Emmy, who uses the excuse that she is "only 3" to avoid being punished for misbehaving. Eventually the family catches on to her pouting and tantrums and she is sent to her room to ponder her behavior.